Is it too late to run away and join the circus? : - Smye, Marti Diane (Hungry Minds, 2002)
In this unique guide, now updated, Marti Smye, Ph.D., gives you targeted tools to take charge of that change—and match your strengths, your beliefs, and life's realities to your dreams. A corporate change management specialist, Smye shows you how to apply the secrets of cutting-edge organizations to your own career and life. With quizzes and checklists at every step, you'll learn how to take inventory, invest in yourself, create your own "board of directors," develop a realistic, flexible business plan—and soar to new heights as the CEO of "You, Inc." Is It Too Late to Run Away and Join the Circus? is filled with uplifting, real-life stories.